ANALISIS KESALAHAN EJAAN BAHASA INDONESIA PADA TEKS LAPORAN HASIL PEROBAAN SISWA KELAS IX - Rosa Rita; Wikanengsih; R. Mekar Ismayani (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study intends to analyze Indonesian spelling errors in grade 9 students' experimental report texts. This research is also motivated by the many Indonesian spelling errors and students' spelling scores in the small test report text assessment criteria.  The method in this research is descriptive qualitative method.  The instruments used in this study were the text of the student's writing test report and the test report text assessment guidelines.  The data collection technique in this study was to look for sentences containing Indonesian spelling errors in the text of student experimental reports. The method of information analysis tried is reading, marking errors, analyzing, then formulating. Subject in this study was the experimental results of class 9D students at SMPN 1 Cikalongwetan, totaling 20 people.  The results of this study showed that out of 20 students in class 9D, 75% of the total number of students in 9D made a capital letter error.  Meanwhile, errors in writing capital letters at the beginning of a sentence reached 55% and errors in writing capital letters in the middle of a sentence reached 35%.  The conclusion of this study is that the cause of Indonesian spelling errors in the text of the class 9D experimental report at SMPN 1 Cikalongwetan is due to students' lack of understanding in Indonesian spelling and the lack of learning about Indonesian spelling in class.